The Psychological Representation of the Madurese People in the Poem "Ibu" by D. Zawawi Imron - Faridi, Moh (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The poem "Ibu" by D. Zawawi Imron serves as a bridge between the poet’s personal experience and the collective experience of the Madurese people. This study aims to analyze the psychological representation of the Madurese community within the poem, identify the embedded social values, and explain the relationship between the poem’s elements and contemporary social realities. The method employed is qualitative analysis using a hermeneutic and content analysis approach. The findings reveal that the poem reflects key psychological characteristics of the Madurese people, such as religiosity, a strong work ethic, and deep respect for the mother figure. The conclusion indicates that although the Madurese community is undergoing social changes, the values portrayed in the poem remain relevant and enduring.